Ice volume changes (1936-1990-2007) and ground-penetrating radar studies of Ariebreen, Hornsund, Spitsbergen - Lapazaran Izargain, Javier Jesús; Petlicki, M.; Navarro Valero, Francisco José; Machío, F.; Puczko, D.; Glowacki, Piotr; Nawrot, A. (Polar Research, 2013)
Ariebreen is a small (0.37 km2) valley glacier located in southern Spitsbergen. Our ground-penetrating radar surveys of the glacier show that it is less than 30 m thick on average, with a maximum thickness of 82 m, and it appears to be entirely cold. By analysing digital terrain models of the ice surface from different dates, we determine the area and volume changes during two periods, 1936-1990 and 1990-2007. The total ice volume of the glacier has decreased by 73% during the entire period 1936-2007, which is equivalent to a mean mass balance rate of -0.6190.17 m/yr w.eq. The glacier thinning rate has increased markedly between the first and second periods, from -0.5090.22 to -0.9590.17 m/yr w.eq.